Metabolic Syndrome and Accelerated Biological Ageing - McCarthy, Kevin (Trinity College Dublin. School of Medicine. Discipline of Medical Gerontology, 2024)
Introduction: Metabolic syndrome consists of the cluster of obesity, insulin resistance, hypertension, and atherogenic dyslipidaemia. This syndrome is a risk factor for all-cause mortality but has not been well characterised in an ageing Irish population. This PhD aimed to determine the prevalence and characteristics of metabolic syndrome in an older Irish population, and to explore its associations with biological ageing to improve the current understanding of the associations with morbidity; the hypothesis being that metabolic syndrome is highly prevalent among older Irish adults and is associated with accelerated biological ageing. Using data from the Irish Longitudinal Study on Ageing (TILDA) (2009-2011 to 2014-2015), this work comprised four studies. Methods: Metabolic syndrome status was determined using TILDA-modified versions of the National Cholesterol Education Program Adult Treatment Panel III and International Diabetes Federation criteria. The first study investigated the prevalence and characteristics of metabolic syndrome using weighted data from wave 1 of TILDA. The second study used incident frailty at a four-year follow-up as a marker for accelerated biological ageing at a systems level – frailty being a condition where one has decreased multi-system physiological reserve and increased vulnerability to stressors. Frailty was operationalised using both frailty phenotype and frailty index. The third study used the GrimAge epigenetic clock as a measure of accelerated biological ageing at a cellular level – GrimAge being a measure of DNA methylation patterns that are associated with increased likelihood of death. This study also explored inflammation (as measured by C reactive protein – CRP) and metabolic dysfunction (as measured by adiponectin) as possible mediating factors in GrimAge age acceleration. The fourth study explored a possible modifiable risk factor for a component of metabolic syndrome – with vitamin D’s potential role in the pathogenesis of insulin resistance being examined. Results: Study one showed that 40% of adults aged 50 years or older in Ireland meet at least one of the two diagnostic criteria for metabolic syndrome examined. Metabolic syndrome was more prevalent among males and increasingly prevalent with age. Lower educational attainment, and lower physical activity levels were also associated with an increased likelihood of metabolic syndrome. In the second study, metabolic syndrome was shown to be associated with both prevalent and incident frailty over a 4-year period, with up to a 57% increased likelihood of frailty. Study three showed that those with metabolic syndrome were older biologically than their chronological age, as measured by GrimAge epigenetic clock, by approximately 4 months for each count of the number of components within the diagnostic criteria. This study also showed that the effect was mediated by inflammation by over 30%, and by 16% by metabolic dysfunction. The fourth study showed that among participants with normoglycaemia at baseline, those with vitamin D deficiency were 62% more likely to have prediabetes at 4-year follow-up compared to those whose vitamin D levels were ≥75nmol/L. Conclusion: These findings show that metabolic syndrome is highly prevalent among older adults in Ireland and is associated with accelerated ageing at both a systems and cellular level. Inflammation mediates the effects of metabolic syndrome. Given the association between vitamin D and prediabetes further interventional trials should be explored to examine if optimising vitamin D status may reduce the likelihood of developing insulin resistance, a key component of metabolic syndrome. Other than preventing the development of metabolic syndrome in the first place, these results highlight the importance of recognising metabolic syndrome and improving the understanding of its associations with pathogenesis with a view to intervening and preventing accelerated ageing and reduced health-span.
Keywords: Metabolic syndrome, Ageing, Prevalence, Frailty, Epigenetics, GrimAge, Inflammation, Insulin Resistance, Vitamin D